“The children of today make the nation of tomorrow” : a social history of child welfare in twentieth century South Africa - Muirhead, Jennifer (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: “The cry of the children of the needy is bitter and heartrending, and any effort towards stilling it deserves the best support and encouragement of the community… every day it rises in despairing appeal for succour and relief.” So wrote a South African newspaper editor in the early 1900s. This “cry” was answered by the emergence of a fledgling child welfare movement in South Africa, largely under the impetus of private charities mimicking international trends – particularly those of the metropole. The 1913 Children’s Act codified child protection, whilst government policies such as child maintenance grants helped in targeting one of the key challenges of child welfare: (white) poverty. Progressively, state and welfare became ever more entwined, epitomised by the formation of the National Council of Child Welfare in 1924 and the Social Welfare Department of 1937. Whilst the state played a constructive role when the aims of child welfare organisations tallied with its own goals (such as eliminating white poverty) it took on a more malevolent form when child welfare organisations did not toe the party-line, by turning their attention from white children to black children in the late 1930s. The movement towards an apartheid state in 1948 saw the consolidation of de facto racial policies into de juro government legislation. This thesis explores the delicate balance between maintaining state support, whilst upholding the values of independent welfare, “irrespective of race or class, of politics or creed”. Despite asserting such inclusive sentiments, borrowed from international discourses, child welfare in South Africa could not be removed from its local socio-political context. The 1953 Bantu Education Act and the 1960 Children’s Act consolidated racial separation through the unequal allocation of state resources to black and white children. Despite the muted concerns of child welfare activists, apartheid discrimination towards African children increased as the century progressed, intensifying hostility and necessitating the agency of African youth towards the apartheid government culminating in the Soweto Uprising of 16 June 1976 and its aftermath. The key aim of this thesis is to illustrate that, while government involvement in welfare brought many benefits to the South African child welfare movement, it simultaneously created a dependence that would make child welfare organisations vulnerable to racialised party politics and bureaucracy in the twentieth century. This is evidenced in the divergence of child welfare along racial lines with white children receiving care similar to that in the Anglophone west, whilst African children were largely neglected. The unequal allocation of resources according to race served to consolidate white hegemony for generations of South Africans, as the “children of today make the nation of tomorrow”.